THE HEALTHCARE SERVICE SYSTEM OF BPJS PARTICIPANTS IN TANGERANG REGENCY - Rully Syahrul Mucharom; Rilla Kusumaningsih (Universitas Muhammadiyah Ponorogo, 2019)
Healthcare service has become the main priority of executors as it is one of the basic rights of the people, and that its service must be established by the government. As mentioned in the Republic of Indonesia’s 1945 Constitution Article 28H paragraph (1) and Article 34 paragraph (3), the government has the obligation to provide proper and worthy healthcare services which suit the needs of the people. A state is an instrument which may give protection for all its citizens through a system built by that state. Economic gaps tend to bring out problems such as poverty and social gaps. Both of them are the central issues of social policies and of the welfare development. In early 2014, right on January 1 st the government of Indonesia through the Ministry of Health has operated the National Healthcare Security Program (Program Jaminan Kesehatan Nasional/JKN). The JKN program has also been applied in Tangerang. One of the focuses of the regional government and the BPJS (Badan Penyelenggara Jaminan Sosial/Social Security Administering Body) in Tangerang Regency is establishing social welfare for its citizens and to start a system of Healthcare Social Security.